The production structure and the dynamics of development - Gérard Ficket; Norberto Gonzalez (CEPAL Review, 1976)
The authors criticize the fallacious concept of an antinomy between import substitution policies and policies to promote the export of manufactures. To regard these as mutually exclusive alternatives poses options geared only to part of the problem, and incapable of providing an adequate answer to development needs. Substitution without exports, carried out within the narrow framework of each national market, leads to inefficiency and high costs. The export of manufactures without substitution maintains the current backwardness in the production of capital goods and essential intermediate goods which is a bar to less dependent and more rapid development and helps to account for Latin America’s present unsatisfactory position in the world economy. The authors show that, in developed economies, the larger the market, the farther industrial development can be taken without any loss of efficiency. In the light of this object lesson, they suggest that if import substitution policies and policies for the export of manufactures were combined through co-operation between the countries of the region, Latin America would attain a better position in the international economy and a much higher level of development.